1984
DOI: 10.1111/j.1464-410x.1984.tb05393.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Vision Internal Urethrotamy. A Critical Review of 365 Operations

Abstract: Internal urethrotomy under direct vision for urethral strictures in the male was employed on 369 occasions in 225 patients during a 4-year period. A retrospective review of results showed an overall cure rate of 77% but the cure rate after each individual operation was less than 50%. Operations for recurrence carried a significantly lower cure rate than initial operations but even after several recurrences there were reasonably good results considering the relatively minor procedure. An active post-operative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
2
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 14 publications
4
34
2
2
Order By: Relevance
“…In our study, in 76.7% patients, the response to optical urethrotomy was good while 6 out of 23 were having poor response. These were quite comparable with Holm Nielsen et al [11] reported success rate 77% & Pansadoro V reported 11% poor results. [12] CONCLUSION During a 5-year period urethral strictures in 23 patients with associated co morbidities were treated by cold knife urethrotomy.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, in 76.7% patients, the response to optical urethrotomy was good while 6 out of 23 were having poor response. These were quite comparable with Holm Nielsen et al [11] reported success rate 77% & Pansadoro V reported 11% poor results. [12] CONCLUSION During a 5-year period urethral strictures in 23 patients with associated co morbidities were treated by cold knife urethrotomy.…”
Section: Discussionsupporting
confidence: 88%
“…With the rise of endoscopic equipment firstly were used in 1865 and IU widely was accepted fort the initial management of short segmental urethral stricture (6). The long term and short term results of IU have been evaluated and the success rate reported as 23-83% in several articles (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not mention how they decided the duration of catheterization and the size of the silicone catheter used. On the other hand, Holm-Nielsen et al [17] , reported an overall cure rate of 77% in the management of 369 strictures in 225 patients and concluded that although an active follow-up with periodic urethroscopic examinations affected the outcome of DVIU; postoperative period of catheterization and positive urine culture at the time of follow-up had no significant influence on the results. As we do not routinely initiate a urethral dilation program after removal of the urethral catheter, we have not enough data to evaluate the effects of post-DVIU dilation on the recurrence rates.…”
Section: Discussionmentioning
confidence: 99%